PENGARUH BRAND AWARENESS, BRAND LOYALTYDAN BRAND PERSONALITY TERHADAP PURCHASEDECISION DENGAN PURCHASE INTENTION SEBAGAIVARIABEL INTERVENING PADA PROVIDER INDOSATDI KOTA SEMARANG - Kieflan Dzilly; Asyhari; Hendar (Universitas Duta Bangsa Surakarta, 2025)
The rapid growth of the telecommunications industry in Indonesia has intensified competition among providers, including Indosat, in influencing consumer purchase decisions. This study aims to analyze the influence of Brand Awareness, Brand Loyalty, and Brand Personality on Purchase Decision with Purchase Intention as a mediating variable among Indosat users in Semarang. The research method is explanatory research using a quantitative approach. The sample consists of 100 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed with multiple linear regression and the Sobel test for mediation analysis. The results show that Brand Awareness, Brand Loyalty, and Brand Personality have a positive and significant effect on both Purchase Intention and Purchase Decision. Furthermore, Purchase Intention is proven to mediate the relationship between the three independent variables and the purchasing decision. These findings suggest that strengthening brand awareness, loyalty, and brand personality should be the focus of Indosat’s marketing strategy to increase consumer buying intentions and decisions. This study provides implications for developing consumer behavior-based marketing strategies in the telecommunications sector.